Effects of the two-pore potassium channel subunit Task5 on neuronal function and signal processing in the auditory brainstem - Saber, Mahshid Helia; Kaiser, Michaela; Rüttiger, Lukas; Körber, Christoph (Frontiers in Cellular Neuroscience, 2024)
Processing of auditory signals critically depends on the neuron’s ability to fire brief, pre-cisely timed action potentials (APs) at high frequencies and high fidelity for prolonged times. This requires the expression of specialized sets of ion channels to quickly repolarize neurons, prevent aberrant AP firing and tightly regulate neuronal excitability. Although crit-ically important, the regulation of neuronal excitability has received little attention in the auditory system. Neuronal excitability is determined to a large extent by the resting mem-brane potential (RMP), which in turn depends on the kind and number of ion channels open at rest; mostly potassium channels. A large part of this resting potassium conductance is carried by two-pore potassium channels (K2P channels). Among the K2P channels, the sub-unit Task5 is expressed almost exclusively in the auditory brainstem, suggesting a special-ized role in auditory processing. However, since it failed to form functional ion channels in heterologous expression systems, it was classified “non-functional” for a long time and its role in the auditory system remained elusive. Here, we generated Task5 knock-out (KO) mice. The loss of Task5 resulted in changes in neuronal excitability in bushy cells of the ventral cochlear nucleus (VCN) and principal neurons of the medial nucleus of the trapezoid body (MNTB). Moreover, auditory brainstem responses (ABRs) to loud sounds were altered in Tasko5-KO mice. Thus, our study provides evidence that Task5 is indeed a functional K2P subunit and contributes to sound processing in the auditory brainstem.